Conservation communautaire et changement de statuts du bonobo dans le Territoire de Bolobo - Victor Narat; Flora Pennec; Sabrina Krief; Jean Christophe Bokika Ngawolo; Richard Dumez (Revue d'ethnoécologie)
There is a diverse range of community-based conservation projects, from a top-down process with projects initiated by national and international institutions to a bottom-up process based on trial and error. In every conservation project, new actors appear, new messages are spread, and each person takes these messages in their own way. As a part of an interdisciplinary study focused on the interactions between bonobos (Pan paniscus), habitats and humans in a community-based conservation area initiated and led by the Congolese NGO Mbou-Mon-tour in the Bolobo Territory (Democratic Republic of Congo), we analyzed the evolution of the local status of bonobos: bonobos as animals with relevance to legal regimes, economic activities, and ecological research and education. Locally, the MMT conservation project has sought to bolster a waning taboo on the eating of bonobos, complementing it with on bonobos and has strengthened it with national and international laws on bonobo protection. Bonobos are thus central to new rules and norms, including the creation of community defined protected forests. Secondly, whereas bonobos were previously widely seen as negative or unnecessary -because not eaten and associated to a bad omen- they are now considered as a driving force for local development. Finally, the interactions between the different actors (local people, conservationists, scientists…) imply a hybridization of traditional and scientific knowledge, contributing to the evolution of the knowledge of each actor. These preliminary results are probably a sign of deeper changes. Our implication in the conservation project and the development of a long-term study site focused on bonobos constitute challenges for the further analysis of the role played by the different actors. In the future, a study by a conservation anthropologist would allow to complete this first analysis and permit a better understanding of the places of conflicts and of collaborations as regards this conservation project.